1968
DOI: 10.1111/j.1360-0443.1968.tb05262.x
|View full text |Cite
|
Sign up to set email alerts
|

Marriage Counseling with Alcoholics and Their Spouses‐II The Correlation of Excessive Drinking Behavior with Family Pathology and Social Deterioration

Abstract: Excessive drinking behavior, family pathology and social deterioration are variables frequently discussed in the literature on alcoholism. Many of the studies which have examined the inter-relationships among the three have reported inconsistent and often contradictory findings. Studies by Pfeffer and Berger;l Gerard, Saenger, and Wile;2 and a paper by Pattison et aL3 present evidence for a consistent relationship between these variables. More recently, Pattison4 has begun to qualify this conclusion. Hill and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Bromet and Moos (1977) found that among married patients, a more positive family milieu was associated with better outcome (drinking, psychological, and social) 6 months after treatment. Similarly, other researchers have reported that higher levels of cohesion and support and lower levels of conflict are associated with more favorable outcome during follow-up periods ranging from 6 to 18 months (Burton & Kaplan, 1968;Finney et al, 1980;Moos, Bromet, Tsu, & Moos, 1979;Orford etal., 1975).…”
Section: Determinants Of the Posttreatment Functioning Of Alcoholic P...mentioning
confidence: 59%
“…Bromet and Moos (1977) found that among married patients, a more positive family milieu was associated with better outcome (drinking, psychological, and social) 6 months after treatment. Similarly, other researchers have reported that higher levels of cohesion and support and lower levels of conflict are associated with more favorable outcome during follow-up periods ranging from 6 to 18 months (Burton & Kaplan, 1968;Finney et al, 1980;Moos, Bromet, Tsu, & Moos, 1979;Orford etal., 1975).…”
Section: Determinants Of the Posttreatment Functioning Of Alcoholic P...mentioning
confidence: 59%
“…Six marital discord and breakdown items from a measure of wives' coping behavior were also predictively associated with 12-month drinking outcome (Orford et al, 1975). Finally, Burton and Kaplan (1968) found that a reduction in the number of areas of disagreement between the alcoholic and his or her spouse was associated with rated improvement in drinking behavior.…”
Section: Posttreatment Influences On Outcomementioning
confidence: 87%
“…The earliest studies described family system‐based models with some cognitive‐behavioral elements, and many reported comparisons of conjoint therapy to other approaches using nonrandomized groups (e.g., comparing outcomes for men in treatment whose wives did or did not participate in sessions). Follow‐ups varied widely in duration, from 6 to 39 months, and typically reported substantially more positive drinking outcomes for men whose wives participated in the treatment than those who did not, as well as improvements in relationship functioning (Burton & Kaplan, , ; Gallant, Rich, Bey, & Terranova, ; Smith, , ). By the mid‐1970s, descriptions of behavioral approaches to conjoint therapy for AUDs began to appear in the literature, and controlled outcome studies of cognitive‐behavioral approaches began in the late 1970s (e.g., McCrady et al., ; O'Farrell, Cutter, & Floyd, ).…”
Section: Description Of Alcohol Behavioral Couple Therapymentioning
confidence: 99%